2013
DOI: 10.1186/1752-0509-7-75
|View full text |Cite
|
Sign up to set email alerts
|

Starch biosynthesis in cassava: a genome-based pathway reconstruction and its exploitation in data integration

Abstract: BackgroundCassava is a well-known starchy root crop utilized for food, feed and biofuel production. However, the comprehension underlying the process of starch production in cassava is not yet available.ResultsIn this work, we exploited the recently released genome information and utilized the post-genomic approaches to reconstruct the metabolic pathway of starch biosynthesis in cassava using multiple plant templates. The quality of pathway reconstruction was assured by the employed parsimonious reconstruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 40 publications
1
50
0
1
Order By: Relevance
“…G1P can be utilized in cellular structure development (cell wall biosynthesis), energy production (respiration) or macromolecule synthesis and accumulation (starch biosynthesis) . According to the KEGG (http://www.genome.jp/kegg) and PMN (http://www.plantcyc.org/) reference pathway databases, starch biosynthesis comprises 270 starch‐related proteins: 141 proteins are annotated in sucrose and starch metabolic reactions, while 129 proteins are involved in the Calvin cycle …”
Section: System Biology Of Cassavamentioning
confidence: 99%
See 2 more Smart Citations
“…G1P can be utilized in cellular structure development (cell wall biosynthesis), energy production (respiration) or macromolecule synthesis and accumulation (starch biosynthesis) . According to the KEGG (http://www.genome.jp/kegg) and PMN (http://www.plantcyc.org/) reference pathway databases, starch biosynthesis comprises 270 starch‐related proteins: 141 proteins are annotated in sucrose and starch metabolic reactions, while 129 proteins are involved in the Calvin cycle …”
Section: System Biology Of Cassavamentioning
confidence: 99%
“…Biosynthesis pathway of cassava starch: Ru5p, ribulose‐5‐phosphate; RuBP, ribulose‐1,5‐bisphosphate; 3PGA, 3‐phosphate‐glycerate; BPGA, 1,3‐bisphospho‐glycerate; GA3p, glyceraldehyde‐3‐phosphate; FBP, fructose‐1,6‐phosphate; F6P, fructose‐6‐phosphate.…”
Section: System Biology Of Cassavamentioning
confidence: 99%
See 1 more Smart Citation
“…In cassava, homologs of bt2 and sh2 have been cloned and their expression pattern determined by northern blot analysis in different tissues (Munyikwa et al 2001). Presence of multiple isoforms of APL genes in cassava is expected (Saithong et al 2013;Dong et al 2019;Tappiban et al 2019), and would be consistent with monocot and dicot plant species (Ballicora et al 2004). In the present study, we identified five isoforms of cassava APL genes (MeAPL1-MeAPL5) from the cassava genome and characterized their functional significance in starch biosynthesis in storage roots using virus induced gene silencing (VIGS).…”
Section: Introductionmentioning
confidence: 98%
“…En yuca, hasta hace poco, sólo algunos de los genes responsables habían sido descritos. Sin embargo con la reciente liberación de la secuencia completa del genoma (Prochnik et al, 2012) fue posible reconstruir la ruta metabólica completa (Saithong et al, 2013). Este estudio mostró que existe un alto grado de conservación en los genes y, en general, en toda la ruta metabólica del almidón de yuca con otras especies como Arabidopsis, arroz, maíz, ricino y papa.…”
Section: Introductionunclassified